2018
DOI: 10.32598/ptj.7.4.197
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Electromyographic Activity of Quadriceps Muscle During Straight Leg Raise in Individuals With and Without Patellofemoral Pain Syndrome

Abstract: This study aimed to investigate the electromyographic activities and balance of Vastus Medialis Obliquus (VMO) and Vastus Lateralis (VL) muscles during Straight Leg Raise (SLR) in individuals with and without Patellofemoral Pain Syndrome (PFPS). Methods: Through an analytical case-control study, 26 persons with PFPS and 26 healthy subjects were recruited by non-random and convenience sampling method. All subjects performed SLR movement. The EMG activity of VMO, VL and VMO/VL ratio were recorded and measured. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…In between-group comparison, no significant difference in the VMO and VL muscle thickness and fiber angle was observed in different positions of SLR maneuver, and the trend of changes in the two groups followed the same pattern by changing the hip rotation with or without ankle dorsiflexor contraction. These results are consistent with the findings of Lotfi et al (2018), who reported no significant difference in the electrical activity ratio of VMO to VL during the SLR maneuver be-tween the healthy and PFPS groups [28]. The lack of between-group difference could be young PFPS patients in the present study with no chronic condition, and the pattern of their knee muscles activity probably did not substantially change compared to healthy individuals.…”
Section: Discussionsupporting
confidence: 93%
“…In between-group comparison, no significant difference in the VMO and VL muscle thickness and fiber angle was observed in different positions of SLR maneuver, and the trend of changes in the two groups followed the same pattern by changing the hip rotation with or without ankle dorsiflexor contraction. These results are consistent with the findings of Lotfi et al (2018), who reported no significant difference in the electrical activity ratio of VMO to VL during the SLR maneuver be-tween the healthy and PFPS groups [28]. The lack of between-group difference could be young PFPS patients in the present study with no chronic condition, and the pattern of their knee muscles activity probably did not substantially change compared to healthy individuals.…”
Section: Discussionsupporting
confidence: 93%
“…The risk factors involved in the pathogenesis of PFPS, are classified into two categories, as intrinsic or extrinsic risk factors. In ----------------------------------------------------------------------------------------Received on 25-10-2021 Accepted on 12-05-2022 addition to this, damage to soft tissue structures for example shortening of lateral retinaculum or decrease in strength of medial retinaculum, decreased elasticity of iliotibial band, stiffness of hamstring and gastrocnemius can directly or indirectly impart greater stress on the patella-femoral joint 10 . Some of these intrinsic risk factors can be varied such as decrease in the length of the quadriceps and plantar flexors most of the times, and decreased length of the hamstrings and the iliotibial band or tensor fascia lata complex 11 .…”
Section: Introductionmentioning
confidence: 99%